Usulan Sistem Penilaian Key Perfomance Indicator dengan Menggunakan Metode AHP, Object Matrix dan Traffic Light System (Studi kasus: PT. Combiphar) - Afifah, Farah; Yogaswara, Budhi; Suwarsono, Litasari Widyastuti (eProceedings of Engineering, 2023)
Abstract-Pharmaceutical companies are the manufacturers of medications and supplements needed by many people. The competition between all the pharmaceutical companies are getting harder and it’s push the needs to managing their internal business process to produce their products up to the regulations and fulfilling the costumers’ expectations. PT. Combiphar is one of the company in the pharmaceutical field. Currently they’re using KPI with the model of balanced scorecard. KPI is a set of measured performance measurement and need a set of monitoring system to make sure it’s remained on the optimum conditions to be a performance measurement tool that is in accordance with company needs. The company currently use a method to set the weight of their KPI based on the top management’s decision in order to set it on each periods. This research’s goals are to discussing the KPI’s weighting method the company currently use, AHP and scoring methods with OMAX and TLS. From this research, there are indications that 42 monthly achievement of KPI are in the red category, 36 monthly achievement of KPI are in the yellow category and 17 monthly achievement of KPI are in the green category. Keywords-performance measurement, KPI, BSC, AHP, OMAX, traffic light system.